Literatura, cidade e violência : uma análise comparativa das experiências urbanas em O Cortiço e Cidade de Deus - (:unkn) unknown (Universidade Estadual de Goiás, 2015)
This research studies the relationship between literature, city and violence, represented in Brazilian novels O Cortiço by Aluísio Azevedo, and Cidade de Deus, by Paulo Lins, published in 1890 and 1997 respectively. Inserted into the line of research "Linguagem e Práticas Sociais", in particular, the research contributes to the field of Literary Studies in comparing these romances, produced at different times and referring to historical and literary contexts also different, but they bring the city of Rio de Janeiro as the privileged space. Through the comparative method, we analyze the experiences of the characters portrayed, the types of dwellings found both in the slum as in the shantytown and the ways of manifestation of violence. Therefore, it considers the city in history and its presence in Brazilian literature and are still focused the issue of violence in the literary text and the outstanding characteristics of urban violence in Brazil. The novels were analyzed on the basis of theoretical and critical works about the city and its elements in Brazilian literature, and discussing the causes and types of urban violence. As the theoretical, were chosen Bosi (2006), Buoro et al. (2010), Calvino (1990), Duarte (2006), Endo (2005), Ginzburg (2012), Gomes (1994), Ignácio (2010), Morais (1981), Mumford (1965), Puty, Barcellos e Daniel (1982), Rolnik (2012), Valladares (2000), Velho (1978), among others. As a result, it appears that the discussed novels recreate, in fiction, the reality of big cities, leading to considerations on the possible causes of the phenomenon of urban violence and its intensification over the years, which has occurred and is occurring together the profound transformation of the city space. It is confirmed, therefore, the present literary texts in question, as they reveal the urban experiences that contribute mainly to the understanding of human and social relations.
Keywords: Literatura; Cidade; Violência; Literature; City; Violence; LETRAS::LITERATURAS CLASSICAS